Bile acids modulate the Golgi membrane fission process via a protein kinase Ceta and protein kinase D-dependent pathway in colonic epithelial cells. - Long, Aideen; Kelleher, Dermot; Byrne, Anne-Marie; Foran, Eilis; Sharma, Ruchika; Davies, Antony; Mahon, Ciara; O'Sullivan, Jacintha; O'Donoghue, Diarmuid (My University, 2010)
Deoxycholic acid (DCA) is a secondary bile acid that modulates signalling pathways in epithelial cells. DCA has been implicated in pathogenesis of colon carcinoma, particularly by activation of the protein kinase C (PKC) pathway. Ursodeoxycholic acid (UDCA), a tertiary bile acid, has been observed to have chemopreventive effects. The aim of this study was to investigate the effect of DCA and UDCA on the subcellular localization and activity of PKCeta and its downstream effects on Golgi structure in a colon cancer cell model. PKCeta expression was localized to the Golgi in HCT116 colon cancer cells. DCA induced fragmentation of the Golgi in these cells following activation of PKCeta and its downstream effector protein kinase D (PKD). Pretreatment of cells with UDCA or a glucocorticoid, dexamethasone, inhibited DCA-induced PKCeta/PKD activation and Golgi fragmentation. Knockdown of glucocorticoid receptor (GR) expression using small interfering RNA or inhibition using the GR antagonist mifepristone attenuated the inhibitory effect of UDCA on Golgi fragmentation. Elevated serum and faecal levels of DCA have been previously reported in patients with ulcerative colitis (UC) and colon cancer. Analysis of Golgi architecture in vivo using tissue microarrays revealed Golgi fragmentation in UC and colorectal cancer tissue. We have demonstrated that DCA can disrupt the structure of the Golgi, an organelle critical for normal cell function. Inhibition of this DCA-induced Golgi fragmentation by UDCA was mediated via the GR. This represents a potential mechanism of observed chemopreventive effects of UDCA in benign and malignant disease of the colon.
PUBLISHED
Keywords: DCA-induced Golgi; Bile acids; Colorectal cancer; Golgi apparatus; Protein kinase; Ursodiol; Colon; Colon cancer; Epithelial cells; Cancer